Bandung’s Image as a Tourist Destination: An Application of Quantitative and Qualitative Approach - Agustinus Februadi; Nono Wibisono; Dewi Purnamasari (Jurnal Internasional Penelitian Bisnis Terapan, 2019)
Bandung is a popular tourist destination in Indonesia and a gateway for tourists who visit destinations around greater Bandung areas. Currently, Bandung is also known as a culinary, shopping, and nature tourism destination. Past studies have measured the image of Bandung as a tourist destination. However, the measurements were done partially due to the use of quantitative method only. Thus, the results were not comprehensive. To resolve the drawbacks of the previous studies, this study used both qualitative and quantitative approaches. Data were collected from 430 domestic tourists by ways of structured and unstructured interviews in 20 different destinations in Bandung and the surrounding. Data were processed by descriptive statistical methods, factor analysis and content analysis. The results of quantitative analysis show that, in term of functional-attribute, Bandung was positively perceived as a destination characterized with natural scenic beauty, many interesting places, and various exotic foods. In terms of the psychological-attribute, Bandung was perceived as the right place for shopping and culinary tourism. The results of qualitative analysis indicate that, functionally, Bandung was a destination with natural scenic beauty, pleasant weather and provide various exotic foods. Psychologically, the tourists experienced calm and tranquil atmosphere, happiness, and comfort.